Assessing hybrid supercapacitor-battery energy storage for active power management in a wind-diesel system - Shayeghi, H.; Monfaredi, F.; Dejamkhooy, A.; Shafie-khah, M.; Catalão, J. P. S. (Elsevier, 2021)
This paper presents an effective hybrid supercapacitor-battery energy storage system (SC-BESS) for the active power management in a wind-diesel system using a fuzzy type distributed control system (DCS) to optimally regulate the system transient. It addresses a new online intelligent approach by using a combination of the fuzzy logic and DCS based on the particle swarm optimization techniques for optimal tuning and reduce the design effort of the control system. This mechanism combines the features of online fuzzy theory and distributed control system (DOFCS), which has a flexible structure. The proposed energy management algorithm for the hybrid SC-BESS is well able to repel the peak-impact of the battery storage system during the wind speed and load changes. The high performance of the suggested methodology is represented on a typical wind-diesel test system.
Keywords: Battery energy storage; Distributed control system; Hybrid energy storage; Power management; Wind diesel system; fi=Sähkötekniikka|en=Electrical Engineering|